Primary swenson′s pull-through in children with chronic constipation: A preliminary report - Bakare Tajudeen I; Badmus T; Lawal A; Katung A (Wolters Kluwer Medknow Publications, 2010)
Background: The discrepancy in diameters of the resected ends coupled with the heavy faecal loads in the colon of chronically constipated children with Hirschsprung′s disease makes definitive primary pull-through procedure quite difficulty in this group. Patients and Methods: Four consecutive patients (aged 5 months to 11 years) who presented with chronic constipation were given warm saline enema along with Castor oil per oram twice daily for 1 week before and 2 weeks after full-thickness biopsies that confirmed Hirschsprung′s disease. All patients had intravenous Cefuroxime or Ceftriaxone plus Metronidazole at induction of anaesthesia. Intra-operatively, the levels of resections were 6-8 cm proximal to the most contractile part of the colon adjacent to the transition zone observed after complete division of mesenteric vessels. Results: There were three males and one female, aged 5 months to 11 years. The levels of aganglionosis were in the rectosigmoid region, except one in the descending colon. There was one case each of anastomotic stenoses, mild enterocolitis and deep peri-anal excoriation. The bowel motions were two to four times daily within 1 month post-operatively. Conclusion: It can be concluded from this preliminary study that with pre-operative saline enema and oral Castor oil for about 3 weeks in chronically constipated children with Hirschsprung′s disease primary pull-through procedures can be performed successfully. However, further prospective work is required with this method.